Why Mahatma Gandhi changed the world forever (Eurasian Journal of Humanities and Social Sciences, 2023)
The article is devoted to understanding the concept of "persistence in truth" (satyagrahi), developed by Mahatma Gandhi in the process of combating English racism and colonialism, why he changed the world.